Covalent Functionalization of Exfoliated Arsenic with Chlorocarbene. (12th October 2018) - Sturala, Jiri; Ambrosi, Adriano; Sofer, Zdeněk; Pumera, Martin
Abstract: Few‐layer and monolayer arsenic (arsenene) materials have been attracting great attention mainly from a theoretical perspective. Chemical modification of these materials would expand significantly the range of their applications. Here, we describe a chlorocarbene‐mediated modification of exfoliated layered arsenic materials. Carbene‐based species are highly reactive and offer further possibilities of functionalization. Our approach for modifying the arsenic surface by chlorocarbene generated from organolithium and dichloromethane resulted in a large surface coverage and a highly luminescent functionalized material, opening the door for its application in modern optoelectronic devices.